Use Of A Multiplex Pcrto Identify Candida, Species In Concentrated Oral Rinse Samples Of Patients With Diabetes - Sampath, M.K.A.; Gunasekera, T.D.C.P.; Kottahachchi, J.; Dilhari, K.A.A.; Bulugahapitiya, U.; Fernando, S.S.N.; Weerasekera, M.M. (Proceedings of International Conference on Multidisciplinary Approaches 2015, 2015)
Attached

Iffrtti Candida infections are most frequently observed in patients withdiabetes. As diabetes has become tiW number one non communicable disease in Sri Lanka, oral Candida infections are an emerging ^tb b lcm Although Candida albicans is the predominant pathogen in oral candidiasis multiple J^ n ilid a speciei; inVolvement is common. Hence it is important to develop rapid, sensitive and specific S filccu lar basbd methods to identify m ultiple Candida species in clinical specimens. Iffjbaim s of this study were to optimizeand apply a multiplex PCR to identify four important Candida I f l t i e s , namely C.albicans, C.parapsilosis, C.glabrata and C.tropicalis in concentrated oral rinse p im p les o f patients with type 11 diabetes. The performance of multiplex PCR was compared with ^plienotypic identification. multiplex PCR was optimized to identify C.albicans, C.parapsilosis, C.glabrata and C.tropicalis concentrated oral rinse samples o f patients with diabetes, attending the Endocrinology clinic at llfblom bo South Teaching hospital. M ultiplex PCR wasoptimized using a common reverse primer, s ;|fS 4 and four species specific prim ers targeting ITS 1 and ITS2 regions o f yeast genome (primer ' c x , CP, and CGL respectively). Optim ized multiplex PCR was applied to identify four different C a n d id a species in 20 clinical samples and the results were compared with results of phenotypic "‘■■'identification for Candida ie; colony characteristics, germ tube test, sugar assimilation and Iflam ydospore formation. Further antifungal susceptibility test was performed using disk diffusion method (NCCLS guideline M 44) for colonized patients. f O u t of the 20 oral rinse samples, 10 were culture positive. However, only 8 samples were colomzed '(> 600 CFU/ml) with Candida species. Out o f these 8 patients, multiple Candida species were ' identified in 5 patients, where all o f them had C. albicansalone with either C. Parapsilosisot C. ■tropicalis. Three patientshad only Candida albicans.The 20 samples tested with multiplex PCR, 14 were positive for Candida spp. All 14 contained C. albicamrmih 12 bemg positive for multiple Candida spp. including C. parapsilosis (10/20), C. tropicalis (4/20) and C. glabrata (4/20). Established multiplex PCR is found to be rapid, sensitive and more specific than conventional culture method in identifying multiple Candida species in oral rinse samples.